Analisis Pandangan Milenial tentang Asuransi sebagai Prioritas Keuangan Utama Menggunakan K-Means dan Decision Tree - Limanauw, Giany Caroline Theresia; Oetama, Raymond (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
Millennials, despite being the largest population segment in Indonesia, show little interest in insurance, with only 6-7% having coverage. This raises concerns about their financial preparedness and protection against unforeseen events. Many lack well-thought-out financial plans, focusing on immediate gratification and overlooking risk management, including insurance. This study aims to discover ways to revive millennials' awareness about the importance of insurance in achieving financial stability and well-being. This study employs a questionnaire for data collection and analyzes the data using k-means and decision tree algorithms. Based on the k-means algorithm and decision tree, it was found that many millennials lack insurance coverage. Reasons include lack of understanding, financial constraints, fear of deception, and considering insurance, not a priority. Young adults aged 21-29 showed a better understanding of insurance, but still, a significant portion remains uninsured. These insights can be used to develop educational programs and communication strategies that aim to bridge the awareness gap and increase insurance literacy among millennials